2019
DOI: 10.3892/or.2019.7115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginsenoside Rg3 on epigenetic modification in ovarian cancer cells

Abstract: Epigenetic modifications are closely related to oncogene activation and tumor suppressor gene inactivation. The aim of this study was to determine the effects of ginsenoside Rg3 on epigenetic modification in ovarian cancer cells. Cell proliferation, metastasis, invasion and apoptosis were respectively determined using Cell Counting Kit-8 (CCK-8), wound healing, Transwell and flow cytometric assays. Methylation levels were determined using methylation specific PCR (MSP). Related-factor expression was detected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Zhao et al found that the increased expression of DNMT3B in ovarian cancer cells increased the methylation level of the promoter regions of anti-oncogenes such as hMLH1 (mismatch repair gene human mutL homolog-1), p16 and p53 . These methylation changes decreased the expression of the hMLH1 , p16 and p53 genes and promoted tumor development [ 42 , 107 ]. As mentioned above, decitabine is a specific DNMT inhibitor, which can partially reverse DNA methylation.…”
Section: Targeting Dnmtsmentioning
confidence: 99%
“…Zhao et al found that the increased expression of DNMT3B in ovarian cancer cells increased the methylation level of the promoter regions of anti-oncogenes such as hMLH1 (mismatch repair gene human mutL homolog-1), p16 and p53 . These methylation changes decreased the expression of the hMLH1 , p16 and p53 genes and promoted tumor development [ 42 , 107 ]. As mentioned above, decitabine is a specific DNMT inhibitor, which can partially reverse DNA methylation.…”
Section: Targeting Dnmtsmentioning
confidence: 99%
“…There is an urgent need for effective prognostic markers to improve OC overall survival ( Powell et al, 2005 ; Shen et al, 2017 ; Tong et al, 2019 ; Zhao et al, 2019 ). Immune cells can enhance anticancer immune responses by recognizing cancer antigens, indicating that they may influence cancer prognosis ( Drakes and Stiff, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, related studies suggested the antiovarian cancer effect of ginsenoside Rg3 (Zheng et al, 2017;Zheng et al, 2018;Liu et al, 2017;. Interestingly, our previous results revealed that ginsenoside Rg3 inhibited cell proliferation, migration and invasion but promoted apoptosis in SKOV3 ovarian cancer cells (Zhao et al, 2019). Moreover, ginsenoside Rg3 decreased hypermethylation of CpG islands in the promoter region of tumor suppressor genes (p53, p16 and hMLH1), reduced the expression levels of DNA cytosine methyltransferases (DNMT1, DNMT3a and DNMT3b), and inhibited the activities of histone deacetylases (HDACs) (Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…Interestingly, our previous results revealed that ginsenoside Rg3 inhibited cell proliferation, migration and invasion but promoted apoptosis in SKOV3 ovarian cancer cells (Zhao et al, 2019). Moreover, ginsenoside Rg3 decreased hypermethylation of CpG islands in the promoter region of tumor suppressor genes (p53, p16 and hMLH1), reduced the expression levels of DNA cytosine methyltransferases (DNMT1, DNMT3a and DNMT3b), and inhibited the activities of histone deacetylases (HDACs) (Zhao et al, 2019). All of these findings suggested that ginsenoside Rg3 may have potential anticancer activity in OC.…”
Section: Introductionmentioning
confidence: 93%